Adaptation to climate change at local level in Europe: An overview. Issue 86 (August 2018) - Aguiar, Francisca C.; Bentz, Julia; Silva, João M.N.; Fonseca, Ana L.; Swart, Rob; Santos, Filipe Duarte; Penha-Lopes, Gil
Graphical abstract: Highlights: Overview and analysis of 147 local strategies for adaptation to climate change in Europe. Development of local adaptation strategies is increasing throughout Europe. Flood protection, water management and urban planning are major response actions. Differing patterns of adaptation planning and adaptive capacity were identified among European regions. Abstract: Europe's climate change vulnerability pushes for initiatives such as the European Adaptation Strategy and the associated Covenant of Mayors for Climate and Energy. What are the triggers and barriers, for which sectors and for which risks and how is adaptation funded? This paper examines 147 Local Adaptation Strategies in Europe. Key triggers were incentives via research projects, implementation of EU policies and the increasing frequency of extreme climate events. Insufficient resources, capacity, political commitment and uncertainty were the main barriers. Prioritized sectors reflected the main local vulnerabilities - flood protection and water management, built environment and urban planning. Differing patterns of adaptation planning and adaptive capacity were identified among different regions in Europe. Large municipalities generally fund adaptation locally, whereas international and national funding appears to be more important for adaptation in less urban or densely populated territories. The database of LAS described in the present study can be expanded and used to increase the understanding of and promotion of local adaptation action in Europe and beyond.